Incidence and predictors of transthyretin cardiac amyloidosis in patients with degenerative aortic stenosis. (3rd October 2022) - Abadie, B; Held, M; Puri, R; Krishnaswamy, A; Yun, J; Hanna, M; Reed, G; Kapadia, S; Jaber, W
Abstract: Background: The approval of new therapies for treating transthyretin (TTR) cardiac amyloidosis has led to significant interest in identifying patients at high risk for this disease. Investigators have identified a correlation between severe degenerative aortic stenosis (AS) and TTR cardiac amyloidosis in older patients, with several studies finding up to 20% of patients who undergo transcatheter aortic valve replacement (TAVR) having TTR cardiac amyloidosis. These initial TAVR studies were conducted when TAVR was performed almost exclusively in high surgical risk populations. Therefore, the true incidence of TTR cardiac amyloidosis in an all-comers with severe degenerative AS referred for TAVR is unknown. Purpose: To identify the true burden of TTR cardiac amyloidosis in a contemporary population of severe degenerative AS undergoing TAVR screening. Methods: All patients ≥70 years with severe native valve degenerative AS seen in a multidisciplinary valve clinic were referred for technetium-99m pyrophosphate cardiac scintigraphy (PYP scan) for evaluation of cardiac amyloidosis. Diagnosis was made via combination of planar grade and heart to contralateral lung ratio, confirmed on single positron emission computed tomography/computed tomography (SPECT/CT). Patients with a positive PYP scan were referred to a heart failure clinic where they underwent testing for AL amyloidosis. Results: Over a 10 month period, 247 patients seen in valve clinic underwent a PYP scan. Of this cohort, 203 patients ultimately underwent TAVR, 15 surgical aortic valve replacement, and 2 balloon valvuloplasty with 27 patients having not yet undergone a procedure. The positivity rate was 4% (10/247) with 1 patient having an equivocal result. The patients with a positive PYP scan had higher rate of low-flow low-gradient (LFLG) AS (64% vs 29%, p=0.006) and classical LFLG AS (27% vs 8%, p=0.02). Echocardiographic measures associated with a positive PYP scan include a lower global longitudinal strain (−10.0% vs −16.1%, p=0.008), lower average e' (4.5 vs 6.5, p=0.003), and an increased E/A ratio (1.8 vs 1.1, p=0.018). Conclusions: The incidence of TTR amyloidosis in a contemporary, severe AS population ≥70 years undergoing TAVR screening appears much lower than previously described in the literature. Echocardiographic traits may be able to predict which patients with severe AS should undergo evaluation for TTR cardiac amyloidosis. Funding Acknowledgement: Type of funding sources: None.